Assessment of Sampling Technique from Feeders on Copper, Zinc, Calcium, and Phosphorus Analysis - A. M. Jones; J. C. Woodworth; C. Vahl; S. S. Dritz; M. D. Tokach; R. D. Goodband; J. M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2017)
While numerous research articles have been published on how to collect a representative sample, and analytical or laboratory-to-laboratory variation, we are unaware of any studies to examine exactly how many samples to collect from feeders, or whether they should be pooled or not to minimize analytical variation. Therefore, this study was designed to evaluate different sampling procedures and the number of samples to collect, and achieve an accurate assessment of nutrient fortification in swine diets. Diet samples were collected from a study evaluating the effects of increasing Cu on growth performance of finishing pigs. Treatments were arranged in a split-plot design with the whole-plot consisting of 1 of 6 concentrations of dietary Cu (27 to 147 ppm total Cu included in the diet) and the subplot using 1 of 2 sampling techniques (probe vs. hand grab). In addition to Cu, samples were also analyzed for Ca, P, and Zn, which were formulated to be the same across diets. A total of 6 feeders per dietary treatment were sampled using a 63 in. brass open handle probe (Seedburo Equipment Company, Des Plaines, IL), which contained 10 openings spaced approximately 2 in. apart. The probe was inserted into the feeder on average 4 times to obtain 2 lb of sample. Alternatively, samples were simply collected by inserting a bare hand into the feeder approximately 8 times to obtain the 2 lb of sample. Within a feeder and sampling technique, subsamples ( 200 g) were created by using a sample splitting device. Next, all samples were ground through a centrifugal mill (0.5 mm screen) and submitted for mineral analysis in duplicate. In addition to the 6 individual feeder samples, a subsample ( 33 g) from each individual feeder was pooled within dietary treatment and sampling technique to form a single composite sample ( 200 g). This process was repeated until 4 individual composite samples were created for each diet and sampling technique. Results indicated that the observed variability when sampling feeders with an open handle probe was reduced (P = 0.013) for Cu and marginally reduced (P = 0.058) for Ca, when compared with hand-sampling. However, no evidence for differences was detected among sampling techniques for Zn and P for the individual feeder analysis. There was no evidence for differences detected among sampling techniques for Cu, Zn, Ca, and P when samples were pooled from 6 feeders to form a single composite sample. While not statistically significant, the overall variability was numerically reduced when pooled from 6 feeders to form a single composite sample. From these results, sampling frequency calculations were determined to assess sampling accuracy within a 95% confidence interval. Results indicated that the number of feeders or composite samples required to analyze was less regardless of Cu, Zn, Ca, and P when using a probe compared to a hand. In summary, these results would suggest that in general, sampling with a probe is associated with less variability on an individual sample basis, but when individual samples are pooled to form a composite sample, there was no difference among sampling techniques. Our results suggest that samples collected with a probe and composited would be the best option to minimize variation and analytical costs.
Keywords: calcium; copper; diet sampling; phosphorus; zinc